Racial Identity and Health Outcomes in an Emerging Latinx Immigrant Community - Henderson, Aasha (Race and social problems, 2024)
Self-reported and street race have been associated with health in the U.S. Race is a social construction based on phenotypical classifications rooted in colonialism. Yet, perceptions of race are different in the U.S. than in Latin America. We investigated relationships between self-reported race, street race (i.e., socially assigned race), and the health of U.S. Latinx immigrants in a community-engaged study of immigrant health in North Carolina. Latinx immigrants aged 18–44 years (N = 391) completed measures of self-reported race, street race, and health. Many participants reported that they did not know their race (n = 171; 44%), although to be eligible all identified as Hispanic or Latino/a/x. No significant relationships were observed between street race and health. For self-reported race, participants who declined to respond to the race question were more likely to have poorer mental health than participants who reported a biracial race and worse physical health than those of unknown, white, biracial, and other races. In exploratory analyses, participants who declined to answer the self-reported race question had higher immigration stress and language stress, were more likely to be undocumented, as well as were less bicultural and were less acculturated to the U.S. than participants in some of the other racial groups. The relationship between race and health among Latinx immigrants is complex and may not be explained by traditional racial and ethnic classifications in the U.S. Future research should explore how Latinx immigrants perceive and construct racial identity in the U.S., how they are racialized, and its impact on health.